How does imported pork regulate the supply and demand of China's pig market during the epidemic?—based on the analysis of African swine fever and COVID-19 - Wang, Jingjing; Wang, Gangyi; Cui, Yiniu; Zhang, Jie (Frontiers in Veterinary Science, 2022)
The pig industry is primarily a domestic industry in China is focused on ensuring the domestic pork supply. This paper analyzed changes in Chinese pork imports following the outbreaks of African Swine Fever (ASF) and COVID-19 between January 2017 to November 2020 and evaluated the impact of imported pork on the development of the swine industry in China. The results demonstrated that the shortage of domestic pork supply changed the import volume. ASF transformed imported pork from a complementary product to meet the diversified needs of domestic consumers into a critical substitute required to fill the supply gap. Following the COVID-19 outbreak, the substitution effect of imported pork decreased. ASF, has caused the supply capacity of pork in China to decrease, the price of pork to increase, leading to increased pork import in January 2019. At the end of 2019, pig slaughter decreased, while China cut tariffs on imported pork. The COVID-19 outbreak did not reduce China's pork imports in China, which declined after the global COVID-19 outbreak. Imported pork has made up for the supply gap during COVID-19, not impacting the level of production of the swine industry in China.